Emerging Research on Adaptive Plants in Karst Ecosystems - Wu, Yanyou (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The global karst distribution area is nearly 22 million km2, accounting for ca. 15% of land area, and the population living in karst areas is approximately one billion. Strong karstification makes the soil environment dry and with high pH and high content of calcium (bicarbonate). The karst environment with a high spatiotemporal heterogeneity seriously affects the growth and development of plants. Faced with these heterogeneous environments, plants have adopted diversified adaptive strategies. This Special Issue is a collection of 15 important research works, which demonstrated some achievements on the physiological and ecological adaption of plants to heterogeneous karst environments, and also explore how to extend the service period of plant resources in karst regions. These works will help to understand the karst-adaptability of plants from multiple perspectives and provide a scientific reference for the selection of karst-adaptable plants and the restoration of vegetation in karst areas. Meanwhile, they will provide theoretical support for organic integration towards economic, social and environmental sustainability of karst areas, and the beautiful vision of "green water and green mountains are golden mountains and silver mountains". In the future, we look forward to more emerging research on adaptive plants in the karst ecosystem, which will serve better in maintaining ecosystems (carbon neutral), ensuring food supply and promoting sustainable social development.